Microbial-induced carbonate precipitation using eggshells and scallop shells as recycled materials - Luma Saleem Raheem; Hussein J. Khadim (Case Studies in Chemical and Environmental Engineering)
Recently, microbial-induced carbonate precipitation (MICP), plays an important role in biogeotechnical engineering applications and is an environmentally friendly bioremediation technique. MICP includes the bioprecipitation of calcium carbonate from media using bacteria and fungi. In this work, the possibility of employing waste products, for instance, eggshells and scallop shells, as alternative-sustainable calcium sources. For MICP to be successful, high urease-producing bacteria had to be locally isolated and selected. Significant urease activity was detected in eight isolates. One isolate identified Bacillus licheniformis which has the greatest urease activity at 13.2 mM urea/min and maximum bioprecipitation activity, was selected. The ability of various calcium sources, to induce carbonate precipitation was tested. A ratio of 1:1 calcium source to urea had the highest carbonate precipitation among these sources. A 1 optical density of cell bacteria produced the maximum carbonate production of 1.7 and 1.4 gm for scallop shells, and eggshells respectively, according to an assessment of the effects of different bacterial concentrations which plays a crucial role in enabling MICP. The optimal pH range for precipitation is between 7 and 8.5 for urea hydrolysis. The precipitates contained calcite crystals with a predilection for crystal morphology, according to XRD, EDS-EDX, and FE-SEM. The potential of using waste products as calcium sources in biogeotechnical engineering is significant, as waste products offer a sustainable and environmentally friendly method for improving the durability of applications such as building and cleanup projects.